Twice as likely to die: The failure of auditing to make an impact on health and safety outcomes in New Zealand - Wassenaar, Brigitta (New Zealand Journal of Health and Safety Practice, 2024)
New Zealanders are twice as likely to be killed at work than Australians and seven times more likely than workers in the United Kingdom (UK). This article explores why health and safety auditing to meet due diligence requirements may not have had the intended impact on occupational health and safety (OHS) outcomes in New Zealand and considers what might be done to improve this.